Study of the temperature rise induced by a focusing transducer with a wide aperture angle on biological tissue containing ribs - 王鑫 林杰兴 刘晓宙 刘杰惠 龚秀芬 (Chinese physics B, 2016)
We used the spheroidal beam equation to calculate the sound field created by focusing a transducer with a wide aperture angle to obtain the heat deposition, and then we used the Pennes bioheat equation to calculate the temperature field in biological tissue with ribs and to ascertain the effects of rib parameters on the temperature field. The results show that the location and the gap width between the ribs have a great influence on the axial and radial temperature rise of multilayer biological tissue. With a decreasing gap width, the location of the maximum temperature rise moves forward; as the ribs are closer to the transducer surface, the sound energy that passes through the gap between the ribs at the focus decreases, the maximum temperature rise decreases, and the location of the maximum temperature rise moves forward with the ribs.